2007
DOI: 10.1074/jbc.m609037200
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Fatty Acid Synthesis in Trypanosoma brucei

Abstract: Whereas other organisms utilize type I or type II synthases to make fatty acids, trypanosomatid parasites such as Trypanosoma brucei are unique in their use of a microsomal elongase pathway (ELO) for de novo fatty acid synthesis (FAS). Because of the unusual lipid metabolism of the trypanosome, it was important to study a second FAS pathway predicted by the genome to be a type II synthase. We localized this pathway to the mitochondrion, and RNA interference (RNAi) or genomic deletion of acyl carrier protein (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(119 citation statements)
references
References 69 publications
5
111
0
Order By: Relevance
“…To (41,42). In line with these reports, we found that in TbCls-knockout parasites incubated in the presence of tetracycline, radioactivity was incorporated into all major glycerophospholipid classes (Fig.…”
Section: Resultssupporting
confidence: 86%
“…To (41,42). In line with these reports, we found that in TbCls-knockout parasites incubated in the presence of tetracycline, radioactivity was incorporated into all major glycerophospholipid classes (Fig.…”
Section: Resultssupporting
confidence: 86%
“…Antiserum specific for lipoylated proteins recognizes a single 40-kDa protein in this stage as well as in procyclic-form parasites (219). As observed in T. gondii, the type II FAS protein ACP is required for proper lipoylation, indicating that lipoate synthesis is responsible for lipoylating the 40-kDa protein.…”
Section: Lipoylated Complexes In Kinetoplastidsmentioning
confidence: 66%
“…This modification occurs at, or near, the site of PE synthesis and temporarily renders eEF1A membrane-bound. Interestingly, plant eEF1A has been reported to incorporate 14 C-labeled fatty acids, however, no direct evidence was provided that eEF1A was modified with an entire PE molecule (11 (49), showed no incorporation of radioactivity into eEF1A (results not shown). However, this is not surprising, because we were unable to detect a PE-modified form of eEF1A by mass spectrometry, and, thus, this form may represent a minor fraction of total eEF1A only.…”
Section: Discussionmentioning
confidence: 95%